Dendritic Organic Electrochemical Transistors Grown by Electropolymerization for 3D Neuromorphic Engineering. Issue 24 (29th October 2021) - Janzakova, Kamila; Ghazal, Mahdi; Kumar, Ankush; Coffinier, Yannick; Pecqueur, Sébastien; Alibart, Fabien
Abstract: One of the major limitations of standard top‐down technologies used in today's neuromorphic engineering is their inability to map the 3D nature of biological brains. Here, it is shown how bipolar electropolymerization can be used to engineer 3D networks of PEDOT:PSS dendritic fibers. By controlling the growth conditions of the electropolymerized material, it is investigated how dendritic fibers can reproduce structural plasticity by creating structures of controllable shape. Gradual topologies evolution is demonstrated in a multielectrode configuration. A detailed electrical characterization of the PEDOT:PSS dendrites is conducted through DC and impedance spectroscopy measurements and it is shown how organic electrochemical transistors (OECT) can be realized with these structures. These measurements reveal that quasi‐static and transient response of OECTs can be adjusted by controlling dendrites' morphologies. The unique properties of organic dendrites are used to demonstrate short‐term, long‐term, and structural plasticity, which are essential features required for future neuromorphic hardware development. Abstract : This paper shows how bipolar electropolymerization can be used to implement structural plasticity, a key ingredient from biological networks known as neurogenesis. Resulting dendritic poly(3, 4‐ethylenedioxythiophene) polystyrene sulfonate (PEDOT:PSS) fibers are further used as organic electrochemical transistors to demonstrate short‐term and long‐term memory effects.